NGOs and lifeworlds in Africa : transdisciplinary perspectives - Kalfelis, Melina C.; Knodel, Kathrin (Berghahn Books, 2021)
"Non-governmental organizations (NGOs) have become ubiquitous in the development sector in Africa and attracting more academic attention. However, the fact that NGOs are an integral part of the everyday lives of men and women on the continent has been overlooked thus far. In Africa, NGOs are not remote, but familiar players, situated in the midst of cities and communities. By taking a radical empirical stance, this book studies NGOs as a vital part of the lifeworlds of Africans. Its contributions are immersed in the pasts, presents and futures of personal encounters, memories, decision-making and politics"--